Neuroprotective mitochondria targeted small molecule restores synapses and the distribution of synaptic mitochondria in the hippocampus of APP/PS1 mice - Noah Keller; Trace A. Christensen; Erik J. Wanberg; Jeffrey L. Salisbury; Eugenia Trushina (Scientific Reports)
Abstract Loss of synaptic activity correlates best with cognitive dysfunction in Alzheimer’s disease (AD). We have previously shown that mild inhibition of mitochondrial complex I with the small molecule tricyclic pyrone compound CP2 restores long-term potentiation and cognitive function assessed by electrophysiology and behavior tests in multiple mouse models of AD. Using serial block-face scanning electron microscopy and three-dimensional electron microscopy reconstruction, we examined the effect of CP2 treatment on synapses, and the distribution and morphology of synaptic mitochondria in the hippocampus of APP/PS1 mice. Structural data confirmed the loss of synapses in APP/PS1 compared to non-transgenic (NTG) littermates. Mitochondrial distribution assessed in pre- and postsynaptic compartments was significantly altered in AD model demonstrating increased presence of mitochondria around dendritic spines compared to NTG mice, indicating the loss of mitochondrial ability to support synaptic function. CP2 treatment restored distribution of synaptic mitochondria and the number of synapses to the NTG control levels. Improved synaptic function in CP2-treated APP/PS1 mice was supported by RNA-seq analysis indicating upregulation of genes involved in axonal guidance, dendritic maturation and synaptic function, and Western blot analysis of brain tissue. Taken together, functional, imaging, biochemistry and structural findings further support the potential of targeting mitochondria as a therapeutic approach for AD.